Changes in the oxygen transport system of erythrocytes in testing the general endurance of students - N.I. Neporadna; S.L. Popel' (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
The aim of the study: to reveal morpho-functional changes in erythrocytes in students with different levels of general endurance. Material and methods: It was examined 80 students (17-19 years old). The students performed a 12-min shuttle run (20m endurance shuttle-run - bleep test). The ventilation function of the lungs was estimated according to the forced exhalation data. The gas composition of the blood was determined by the gas analyzer ОРТІ ССА-TS. Results. It was determined that in students with lower than average and low levels of general endurance, the increase of lungs ventilation is stipulated by the increase in the frequency of respiration. This leads to rapid tiredness of the respiratory muscles, reduces ventilation of the lungs and gas exchange. Low levels of blood oxygenation, intensity of oxidative phosphorylation and ATP resynthesis lead to the appearance of atypical forms of erythrocytes. It is established that at the low level of cardiorespiratory endurance there is an increase in the concentration of acidic metabolism products in arterial blood and reduce in its alkaline reserves. Conclusions. Students with below average and low levels of physical fitness are characterized by: increased respiratory rate, reduced ventilation of the lungs and gas exchange. This leads to the formation of a hypoxic condition in the peripheral blood: a reduce of pO2, pCO2 level and the appearance of metabolic acidosis symptoms. For students with below average and low level of physical fitness hypoxic condition leads to violation of bioenergetic processes in peripheral blood erythrocytes, reduction of ATP product, increase in the content of intra-erythrocytic 2,3-BPG.